The Implementation of Problem Solving toward Critical Thinking Skill of Students in Motion System Subconcepts - Nur Izzatil Afifah; Aminuddin P. Putra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Research on learning outcomes and critical thinking skills has been conducted on student of class XI MIPA 2 SMAN 4 Banjarmasin in motion system subconcepts, that is kind of motion system and abnormality of motion system. The aims of this research is to 1). test the effect of implemenation of problem solving toward cognitive learning outcomes (including affective and psycomotor learning outcomes), 2) describe the effect of implementation of problem solving model toward critical thinking skills of students. The research method designed with a quasi-experimental design for study the results of cognitive and analytical method for affective learning outcomes; psychomotor; as well as critical thinking skills.The samples were 36 students of class XI MIPA 2 as a treatment class and 36 students of class XI MIPA 1 as a control class. Technique of data analysis used for the analysis of the cognitive learning outcomes covariance using SAS 6.04 and for critical thinking skills is descriptive analysis. The results showed 1). cognitive learning results showed a significant difference between students in treatment and control class (F-ratio = 32,44; P = 0,0001; C.V. = 9,001) with 48% influence, 2) Affective learning outcomes for behavior character of students quite satisfactory and social skills as very good, 3) Psychomotor learning outcomes of students classified as good. 4) The results of critical thinking skill of students classified as good.Keywords: problem solving, critical thinking, motion system